2015
DOI: 10.1088/1748-0221/10/12/t12006
|View full text |Cite
|
Sign up to set email alerts
|

Spectral response evaluation of plastic rod scintillators as position sensitive beta particle detectors

Abstract: In this work, a simple position sensitive detector based on rod plastic scintillators was developed for detection of beta particles. The detection setup consisted of a plastic-based rod detector (BC400) coupled to a PMT at one side. A Promethium-147 having about 7 mCi activity was used as a beta particle source. It was shown that the spectral response of this detector can provide useful information about the incident position of the beta particles. K: Scintillators, scintillation and light emission processes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The resolution phantom was also made of 4 iron rods with different diameters (1 cm, 2 cm, 3 cm and 4 cm) and the same lengths (20 cm). 36 projections were recorded for each phantom with a rotation step of 10 • , each in 120 s. The cross-sectional images were reconstructed using Maximum-Likelihood Expectation-Maximization (MLEM) Algorithm [8].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resolution phantom was also made of 4 iron rods with different diameters (1 cm, 2 cm, 3 cm and 4 cm) and the same lengths (20 cm). 36 projections were recorded for each phantom with a rotation step of 10 • , each in 120 s. The cross-sectional images were reconstructed using Maximum-Likelihood Expectation-Maximization (MLEM) Algorithm [8].…”
Section: Methodsmentioning
confidence: 99%
“…One type of the detectors that can be employed in such tomography systems are high aspect ratio scintillators. The possibility of detecting the incident position of gamma-rays with scintillation rod detectors has already been studied and investigated [7][8][9][10]. This ability of the rod scintillators makes them as a candidate for employing in gamma/x-ray industrial computed tomography systems suitable for large objects.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that this type of scintillator is inherently positionsensitive and can be employed as linear detectors for gamma/x-ray imaging and tomography purposes. In the proposed system, we used inorganic scintillators (such as NaI(Tl) or CsI(Na)) instead of organic scintillators (such as plastic or liquid scintillators) because the organic scintillators have a low atomic number and therefore their absorption efficiency is lower than the inorganic scintillators [24]- [27]. Furthermore, due to their small photoelectric cross-section, these scintillators do not show photopeak in their spectral response.…”
Section: Introductionmentioning
confidence: 99%
“…The plastic scintillators have found several applications in different scientific areas [1][2][3][4][5]. The spectral response of the plastic scintillators is an indicative of a major disadvantage facing the gamma rays: the lack of the photopeak in their output gamma spectrum for the energies more than 100 keV [5][6][7].…”
Section: Introductionmentioning
confidence: 99%